Pendampingan Mahasiswa Fakultas Hukum Universitas Achmad Yani Banjarmasin dalam Penggunaan Aplikasi Sitasi Mendeley dan Zotero untuk Pencegahan Plagiasi Karya Ilmiah: Mentoring Students of the Faculty of Law Achmad Yani University Banjarmasin in Using the Mendeley and Zotero Citation Applications to Prevent Plagiarism of Scientific Papers - Qamariyanti, Yulia; Tavinayati, Tavinayati; Zakiyah, Zakiyah; Rahmawati, Diana; Syahrida, Syahrida; Saprudin, Saprudin (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
A scientific work is a written document that aims to elucidate a scientific discourse conducted by an author or researcher. To convey information to the readers logically and methodically. Scientific works are typically composed to seek answers and to validate the veracity of the subject matter addressed. Thus, it is fitting that scientific writing frequently addresses issues that are novel, relevant, and previously unexplored by others. Scientific writing, as delineated by its formal attributes, encompasses papers (for seminars or symposia), articles, practicum reports, theses, and dissertations, all of which fundamentally result from scientific endeavors. The facts, conclusions, and other information inside the scientific study serve as references for other researchers doing subsequent investigations or studies. The aims of implementing community service are, firstly, to equip students with the knowledge and skills to utilize the Mendeley and Zotero citation software for composing scientific papers; secondly, to educate students on methods to prevent plagiarism in academic writing.